Interdisciplinary Collaboration between Public Administration and Agribusiness in Local Wisdom-Based Local Economic Development: Perspective from a Case Study of Ternate City, North Maluku - Sofjan Alizar Sam; Rukiaty Usman; Subchan Mardan (JURNAL SAINS SOSIAL DAN HUMANIORA (JSSH), 2025)
This article explores interdisciplinary collaboration between state administration and agribusiness in local economic development based on local wisdom in Ternate City, North Maluku. Ternate City has abundant natural resource potential, particularly the agribusiness (spice) sector, which in 2021 contributed 18.5% of GDP. This collaboration is considered crucial for maximizing potential and addressing resource management challenges. The role of state administration includes creating supportive policies, providing infrastructure, and providing training and extension programs to build farmer capacity. Data shows that extension programs have successfully increased clove yields. Agribusiness, on the other hand, must integrate local wisdom, such as traditional agricultural practices (e.g., the use of organic fertilizers or intercropping systems), which have been proven to increase farmer productivity and income. Furthermore, this collaboration supports cultural preservation through the promotion of local products, such as through the Ternate Clove Festival. Despite challenges such as a lack of coordination, integrated collaboration between the government, community, and private sector, based on local wisdom, holds significant potential for improving product competitiveness and the well-being of the Ternate community.